Thought-Forms Gone Rogue: A Theory for Psi-Critics and Parapsychologists - Parker, Adrian (Journal of Scientific Exploration, 2021)
It is argued that psi-critics Reber and Alcock have lifted the debate from the impasse concerning the evidence for the existence of psi phenomena, toward focusing on understanding the nature of the phenomena. This focus concerns the demand to show that statistical findings are not anomalies but reflect real cause and effect relationships and to find a common theoretical framework for what otherwise appear to be heterogeneous rogue phenomena. It is maintained here that the demand for showing causal relationships is already met by a methodology using real-time recordings of changing target imagery along with receiver mentation. The demand by critics for a theoretical understanding linking all or most of the rogue phenomena, led to the proposition advanced here concerning thought-forms and co-conscious states. According to this, the many “rogue phenomena” both in psychology and parapsychology (such as automatic writing, lucid dream characters, spirit possessions, and entity experiences in psychedelic states) are to be understood as representing dissociated thought-forms with varying degrees of co-consciousness and in some cases the development of a genuine degree of autonomy and identity. Keywords: altered states, thought-forms, consciousness, psi, skepticism, automatic writing, co-consciousness, possession